2021
DOI: 10.3390/plants11010026
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese Common Bean Natural Variation Helps to Clarify the Genetic Architecture of the Legume’s Nutritional Composition and Protein Quality

Abstract: Common bean is a nutritious food legume widely appreciated by consumers worldwide. It is a staple food in Latin America, and a component of the Mediterranean diet, being an affordable source of protein with high potential as a gourmet food. Breeding for nutritional quality, including both macro and micronutrients, and meeting organoleptic consumers’ preferences is a difficult task which is facilitated by uncovering the genetic basis of related traits. This study explored the diversity of 106 Portuguese common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The arginine and the homoarginine produced enzymatically, from arginine and lysine, by AGAT (arginine: glycine amidinotransferase) activity have been negatively associated with adverse cardiovascular events and cardiovascular mortality [ 39 ]. Although the protein characterization was performed in just one environment, the considerable variability detected among the studied traits in Córdoba highlights the genetic richness of the studied grain legume collections and at least their potential for specific local breeding [ 17 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The arginine and the homoarginine produced enzymatically, from arginine and lysine, by AGAT (arginine: glycine amidinotransferase) activity have been negatively associated with adverse cardiovascular events and cardiovascular mortality [ 39 ]. Although the protein characterization was performed in just one environment, the considerable variability detected among the studied traits in Córdoba highlights the genetic richness of the studied grain legume collections and at least their potential for specific local breeding [ 17 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…11,55,56 Comparatively, a much higher average RS content of 45.23% was observed in the Córdoba region compared to the 30.74% in the Cabrela region in 106 kidney bean accessions from Portugal. 57 Heat stress exposure in Córdoba may contribute to the higher RS content than the mild climate environment in Cabrela. The abovementioned observations suggest that both the genotype and planting environment influence the carbohydrate content and distribution, and particularly heat stress contributes to RS accumulation during seed filling.…”
Section: Reviewmentioning
confidence: 99%
“…A wealth of conditions including site of cultivation, milling procedure, moisture, genotype, cooking, fermentation, leavening agent and storage conditions can affect RS concentration in beans (Kutos et al ., 2003; Martín‐Cabrejas et al ., 2004; Vargas‐Torres et al ., 2004a, 2004b, 2006; Aguilera et al ., 2009; Yadav et al ., 2010a; Li et al ., 2011; Ovando‐Martínez et al ., 2011b; Piecyk et al ., 2012, 2013; Liu et al ., 2013; Arce‐Arce et al ., 2014; Hooper et al ., 2017, 2019, 2021; Santiago‐Ramos et al ., 2018; Escobedo et al ., 2020; Bento et al ., 2021; Loader et al ., 2021; Mendes et al ., 2021; Choe et al ., 2022; Guldiken et al ., 2022). However, studies on the role of the agronomic management on the RS concentration are almost absent, with the exception, in the present work, of two reports on the water availability (Herrera et al ., 2021; Salas‐Lumbreras et al ., 2023), both of which found that terminal drought, but not a restricted irrigation during the whole cycle, reduced the RS concentration in two common bean genotypes compared to a full irrigation during the whole cycle.…”
Section: Rs In Phaseolus and Its Variation Due To The Food Treatmentmentioning
confidence: 99%
“…Notably, a recent genome wide association mapping highlighted 4 genetic markers of the RS concentration in a bean population composed of 106 accessions from Portugal grown in a multi‐environmental trial (Mendes et al ., 2021). The latter authors showed that varying the environment consisted in a variation from 30.7% ± 3.5% to 45.2% ± 11.4%, with higher values in drier areas and with only mild differences in the seed moisture, across the genotypic set used.…”
Section: Rs In Phaseolus and Its Variation Due To The Food Treatmentmentioning
confidence: 99%